Photoconverter with luminescent concentrator. Matrix material - Kulish, M.R.; Kostylyov, V.P.; Sachenko, A.V.; Sokolovskyi, I.O.; Shkrebtiy, A.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2019)
Materials promising for the production of luminescent solar energy concentrators were considered. It is known that the silicon oxide matrix is transparent within the spectral range where the Sun emits light. To date, the low-temperature sol-gel method for synthesizing SiO₂ coatings with the simultaneous doping of the material with quantum dots (QDs) has been developed. The transmission spectrum of borosilicate glasses (BK7) is narrower than that of SiO₂. Typically, the doping of BK7 with the quantum dots of the group AᶦᶦBᵛᶦ is carried out using the method of condensation at high temperatures, which results in a low value of the quantum yield of luminescence. Minimal losses of luminescent quanta through the leakage cone will be in the matrix of glass LASF35 022291.541, whose refractive index is 2.022. In the research of the properties of photoconductors with a luminescent concentrator, the matrix is most often made of polymethylmethacrylate (PMMA). Its doping with QDs and dyes is well developed. The quantum yield of luminescence of luminophores when doping PMMA with dyes and QDs is close to unity. The magnitude of losses of luminescent quanta in matrices of glass, PMMA, and silica has been estimated. The dependence of these losses in the wave range, which should be taken into account in the study of stacked fluorescent concentrators, has been analyzed.